2014
DOI: 10.1186/scrt505
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of autologous bone marrow buffy coat grafting combined with core decompression in patients with avascular necrosis of femoral head: a prospective, double-blinded, randomized, controlled study

Abstract: IntroductionAvascular necrosis of femoral head (ANFH) is a progressive disease that often leads to hip joint dysfunction and even disability in young patients. Although the standard treatment, which is core decompression, has the advantage of minimal invasion, the efficacy is variable. Recent studies have shown that implantation of bone marrow containing osteogenic precursors into necrotic lesion of ANFH may be promising for the treatment of ANFH.MethodsA prospective, double-blinded, randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
158
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(161 citation statements)
references
References 26 publications
0
158
0
3
Order By: Relevance
“…Ma et al (2014) reported a statistically significant improvement (p < 0.001) in the cell therapy group at final follow-up compared to the baseline situation, with respect to the level of pain and joint symptoms.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Ma et al (2014) reported a statistically significant improvement (p < 0.001) in the cell therapy group at final follow-up compared to the baseline situation, with respect to the level of pain and joint symptoms.…”
Section: Resultsmentioning
confidence: 84%
“…3 of the studies were randomized control trials (RCTs) (Sen et al 2012, Zhao et al 2012, Ma et al 2014), 1 was a prospective control study (Gangji et al 2011), and the remaining 3 were retrospective case-control studies (Yamasaki et al 2010, Lim et al 2013, Liu et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations